Does Gap Opening and Planting to Rehabilitate the Degraded Tropical Natural Forests Affect the Forest Composition and Structure? - Elias; Bintang C. H. Simangunsong (Jurnal Manajemen Hutan Tropika, 2022)
By 2020, there were 33.4 million ha of degraded forests in Indonesia. If it is not rehabilitated, there will be land-use changes that significantly affect its biodiversity and environment. Gap opening and planting is an important silvicultural regeneration method to rehabilitate degraded tropical natural forests. We studied the subject in a 10 ha degraded lowland tropical natural forest in Central Borneo, Indonesia. The study aims to compare the composition and structure of degraded tropical natural forests before and after gap opening and planting. The methods used consist of 1) gap opening and planting with a proportion of the total gap area to the total degraded natural forest area of 40%; 2) vegetation analysis to assess the composition and structure of forest. The results showed that the gap opening and planting activities led to a decrease in the density of seedlings, saplings, poles, and trees, and cause loss of two species at seedling level and one species at sapling level. The analysis results of the stand structure and species composition, index of species diversity, species evenness index, and community similarity index before and after gap opening and planting of the degraded forest in the study area of 10 ha showed that there is no changes of these variables. These results showed that the use of the gap opening and planting method in the rehabilitation of degraded forests is able to maintain the stability of species composition and stand structure, species diversity, species evenness, and forest communities. In conclusion, the study provided significant empirical results on the composition and structure of degraded tropical natural forests before and after gap opening and planting, which would be instrumental for the development of rehabilitation strategies. It is recommended that the rehabilitation of degraded tropical natural forests in Indonesia can be carried out using the gap opening and planting method.